Developing A Animated Video Integrated With Sidoarjo Local Wisdom For Teaching Descriptive Text In Seventh Grade Using Addie Model - Susilowati, Putri Ayu; Laili, Muawwinatul (Equilibrium: Jurnal Pendidikan, 2024)
Learning media has an important role in this era due to advancements in technology that have transformed the way we learn and access information. The aims of this research are: 1) To describe the process of developing animated video integrated with Sidoarjo local wisdom for teaching descriptive text. 2) To describe the product development of animated video integrated with Sidoarjo local wisdom for teaching descriptive text. 3) To determine the implementation of the development of animated video integrated with Sidoarjo local wisdom for teaching descriptive text. 4) To determine students' responses to the development of animated video integrated with Sidoarjo local wisdom for teaching descriptive text. The research design used in this study is development research, and the ADDIE model was employed for the research procedure. Questionnaires and documentation were used for data collection. The result of the research is an animated video media integrated with Sidoarjo local wisdom received high percentage from media experts gave it a 93% rating, while material experts rated it at 100%, both classified as excellent. Furthermore, the student response to the animated video was positive, with students expressing their interest in using this learning media for descriptive text. In conclusion, the animated video can effectively be used to teach descriptive text in seventh-grade and provides them with insight into the cultural of Sidoarjo.